(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2024)
This study aims to describe the Implementation of Accountability, Transparency, Participatory and Discipline in the Management of Village Fund Allocation in Selong Belanak Village, West Praya District, Central Lombok Regency, West Nusa Tenggara Province. The method used in this study is qualitative descriptive. The data collection techniques in this study are interviews, observations and documentation. The results of the study show that Selong Belanak Village is quite good at meeting the principles of accountability, transparency, participatory and budget discipline in village finance management based on Permendagri Number 20 of 2018, it can be proven that in village financial management, the government has implemented the principle of accountability, namely, every transaction recording by the finance head, both receipts and expenditures are carried out by the finance head. Then the implementation of transparency has been appropriately proven by the installation of billboards at the Selong Belanak Village Office. In the implementation of participation, it is appropriate as evidenced by every activity, always involving the local community in activities carried out by the government. Finally, the implementation of budget discipline is appropriate, as evidenced by the implementation of development in accordance with what has been budgeted by the Selong Belanak village government.